Foot posture is associated with morphometry of the peroneus longus muscle, tibialis anterior tendon, and Achilles tendon. Issue 3 (10th January 2013) - Murley, G. S.; Tan, J. M.; Edwards, R. M.; De Luca, J.; Munteanu, S. E.; Cook, J. L.
<x xml:space="preserve">Abstract</x> The aim of this study was to investigate the association between foot type and the morphometry of selected muscles and tendons of the lower limb. Sixty‐one healthy participants (31 male, 30 female; aged 27.1 ± 8.8 years) underwent gray‐scale musculoskeletal ultrasound examination to determine the anterior‐posterior (AP) thickness of tibialis anterior, tibialis posterior, and peroneus longus muscles and tendons as well as the Achilles tendon. Foot type was classified based on arch height and footprint measurements. Potentially confounding variables (height, weight, hip and waist circumference, rearfoot and ankle joint range of motion, and levels of physical activity) were also measured. Multiple linear regression models were used to determine the association between foot type with muscle and tendon morphometry accounting for potentially confounding variables. Foot type was significantly and independently associated with AP thickness of the tibialis anterior tendon, peroneus longus muscle, and Achilles tendon, accounting for approximately 7% to 16% of the variation. Flat‐arched feet were associated with a thicker tibialis anterior tendon, a thicker peroneus longus muscle, and a thinner Achilles tendon. Foot type is associated with morphometry of tendons that control sagittal plane motion of the rearfoot; and the peroneus longus muscle that controls frontal plane motion of the rearfoot. These findings may be related to differences in tendon loading during gait.